Financial and administrative aspects of harmonization of modern principles of construction industry development in the process of strategic management of company transformations - Fesun , A.; Legkov, V.; Kuzmich, Ya.; Kuznietsov , O. (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the analysis of financial and administrative aspects of harmonization of modern principles of construction industry development in the process of strategic management of company transformations. The work examines the importance of integrating financial and management strategies within the framework of changes taking place in the construction market. Today, the construction industry is faced with the need for constant updating of organizational structures and adaptation to new economic and technological realities. These changes require companies to be able to respond quickly to market changes, scientifically assess financial risks and ensure effective resource management. Thanks to the development of new technologies and innovative approaches, construction companies can optimize their management strategies, increase resource efficiency, reduce costs and maximize profits. An important aspect of the successful implementation of strategic changes is the correct organization of management functions, which includes financial management, planning, control and evaluation of results. In addition, management and financial decisions should be focused on ensuring the long-term development and sustainability of the company in a dynamic market. One of the key tools for achieving strategic goals is the harmonization of the principles of development of construction enterprises, taking into account financial, technical and administrative aspects. The transformation of companies should be based on clearly defined financial goals that will help optimize costs, increase the efficiency of business processes and maximize the return on investment. An important component of the transformation is ensuring continuous improvement of management processes and adaptation to a changing external environment. The article focuses on the need for effective use of financial and administrative tools to harmonize all aspects of the activities of construction enterprises. Development of a system of financial and management indicators, monitoring their implementation and adjusting strategies in real time contribute to the successful implementation of transformations.